2021
DOI: 10.1016/j.agwat.2021.107038
|View full text |Cite
|
Sign up to set email alerts
|

Crop water requirements and crop coefficients for jute mallow (Corchorus olitorius L.) using the SIMDualKc model and assessing irrigation strategies for the Syrian Akkar region

Abstract: Jute mallow (Corchorus olitorius L.) is an annual crop grown for human consumption of its nutritious leaves in many regions of the world. Despite its importance for household food security and farmers' income, reliable information on the crop's water requirements is still quite scarce. To overcome this knowledge gap, the irrigation needs of jute mallow grown in the Akkar region in Syria were investigated. The analysis focused on a three-year period (2017)(2018)(2019) where the SIMDualKc model was calibrated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…Issues related to the quality of the measured dataset and the empirical one-dimensional modeling approach used here to describe the soil water balance in a three-dimensional drip irrigation system may also help explaining why the goodness-of-fit indicators are not as high as in former studies, e.g., Paço et al [88]. Nevertheless, the reported goodness-of-fit indicators are within the range of values reported in the literature for soil water content simulations of field crops [89,90], vegetable crops [91,92], and perennial crops [58][59][60][61] using the same model.…”
Section: Model Performancesupporting
confidence: 63%
“…Issues related to the quality of the measured dataset and the empirical one-dimensional modeling approach used here to describe the soil water balance in a three-dimensional drip irrigation system may also help explaining why the goodness-of-fit indicators are not as high as in former studies, e.g., Paço et al [88]. Nevertheless, the reported goodness-of-fit indicators are within the range of values reported in the literature for soil water content simulations of field crops [89,90], vegetable crops [91,92], and perennial crops [58][59][60][61] using the same model.…”
Section: Model Performancesupporting
confidence: 63%
“…The soil was Vertisol [56], with the main physical and chemical properties given in Table 2. The sampling details and methodologies used in the determination of soil properties were identical to those reported in Darouich et al [52,53] and can be found in those publications. A subsurface drainage network was buried at depths of 1.25-1.75 m, with drainpipes spacing 15-25 m, to collect excess water.…”
Section: Experimental Design and Treatmentsmentioning
confidence: 96%
“…The first part of this research study (hereafter referred to as Experiment 1 or E1) was performed from 2007 to 2011, while the second part (Experiment 2 or E2) was developed from 2015 to 2017 (Table 1). Previous studies [52,53] performed in the same research station aimed at estimating the crop coefficients of zucchini squash (Cucurbita pepo L.) and jute mallow (Corchorus olitorius L.) under different irrigation regimes were developed in fields close to the one now used.…”
Section: Field Experiments 211 Description Of the Study Sitementioning
confidence: 99%
See 2 more Smart Citations